2011
DOI: 10.1002/eat.20788
|View full text |Cite
|
Sign up to set email alerts
|

Mediators between perfectionism and eating disorder psychopathology: Shape and weight overvaluation and conditional goal‐setting

Abstract: The findings support the conclusion that the relationship between SOP and ED psychopathology in women with a clinically diagnosed ED is mediated by shape and weight overvaluation and CGS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 57 publications
(63 reference statements)
0
16
0
1
Order By: Relevance
“…Further, although both SOP and socially prescribed perfectionism (SPP), which loads onto the perfectionistic concerns factor, have been linked to psychopathology generally (e.g., Bastiani, Rao, Weltzin, & Kaye, 1995;Cockell et al, 2002), SOP is linked more with anorexia nervosa (AN) than other disorders, such as anxiety or depressive disorders (Castor-Fornieles et al, 2007). Importantly, SOP, but not SPP, has been found to be specifically related to restriction (Bardone-Cone et al, 2007;Watson, Raykos, Street, Fursland, & Nathan, 2011). This suggests that the SPP-restriction relationship reported in some studies may be spurious, and the result of shared variance with SOP.…”
Section: Perfectionistic Strivings Perfectionism and Restrictionmentioning
confidence: 97%
“…Further, although both SOP and socially prescribed perfectionism (SPP), which loads onto the perfectionistic concerns factor, have been linked to psychopathology generally (e.g., Bastiani, Rao, Weltzin, & Kaye, 1995;Cockell et al, 2002), SOP is linked more with anorexia nervosa (AN) than other disorders, such as anxiety or depressive disorders (Castor-Fornieles et al, 2007). Importantly, SOP, but not SPP, has been found to be specifically related to restriction (Bardone-Cone et al, 2007;Watson, Raykos, Street, Fursland, & Nathan, 2011). This suggests that the SPP-restriction relationship reported in some studies may be spurious, and the result of shared variance with SOP.…”
Section: Perfectionistic Strivings Perfectionism and Restrictionmentioning
confidence: 97%
“…This maladaptive style of functioning is related to many problems in everyday life. OCPD can be linked with other mental health disabilities such as eating disorders (Watson, Raykos, Street, Fursland, & Nathan, 2011), depression and anxiety (Moser, Slane, Burt, & Klump, 2012), and completed suicide in men (Schneider et al, 2006). The dysfunctional lifestyle among people with OCPD is very often at the expense of flexibility, openness and efficiency (Colman, 2009) as well as interpersonal relations (Cain, Ansell, Simpson, & Pinto, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, Appearance Evaluation moderated the association between Cyber victimization and the ED psychopathology. All the variables had theoretical and empirical support justifying their inclusion in the analysis: Appearance Evaluation was associated with eating disorder psychopathology (e.g., Watson et al, 2011 ); Overweight Preoccupation is an important risk factor for eating disorders (Fairburn, 2008 ); and Cyber victimization was the main variable studied in our research. Thus, our results are consistent with another study that found Cyber victimization to be associated with the frequency of dieting to lose weight in adolescents (Ramos-Salazar, 2017 ).…”
Section: Discussionmentioning
confidence: 87%